Adult Attachment and Approaches to Activity Engagement in Chronic Pain - Nicole E Andrews; Pamela J Meredith; Jenny Strong; Genevieve F Donohue (Pain Research and Management)
BACKGROUND: The way in which individuals with chronic pain habitually approach activity engagement has been shown to impact daily functioning, with both avoidance of one’s daily activities and overactivity (activity engagement that significantly exacerbates pain) associated with more pain, higher levels of physical disability and poorer psychological functioning.